UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN KIMIA MELALUI METODE PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS XI IPA 3 SMAN 1 PASAMAN - Neviyanti Neviyanti (STKIP Pesisir Selatan, 2020)
Based on the learning outcomes of students of Class XII Science.3 SMAN 1 Pasaman in Chemistry sub subjects Explaining the equilibrium reaction in the relationship between reagents and reaction results is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in Chemistry. Explaining the equilibrium reaction in the relationship between reagents and reaction results is still very low through Discovery Learning Learning Method in class XI IPA 3SMAN 1 Pasaman Pasaman Barat Regency.This research is a classroom action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 33 students of class XI IPA 3 of SMAN 1 Pasaman. Research data were collected using observation sheets and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been stated, it can be concluded that the Discovery Learning Method can improve student learning outcomes in the sub subjects Describe the structure, method of writing, nomenclature, the nature and use of benzene and its descent. At SMAN 1 Pasaman.Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 50.8 (enough) increased to 84.73 (good) with an increase of 33.93%.